SPECTREPlex: an automated, fast, high-resolution enabled approach for multiplexed cyclic imaging and tissue spatial analysis - Michael D. Anderson; Abigail Plone; Jeffrey La; Madison Wong; Krishnan Raghunathan; Jocelyn A. Silvester; Jay R. Thiagarajah (Communications Biology)
Abstract Mapping the spatial organization of tissues is critical to understanding organ biology in health and disease. Developments in multiplexed antibody-based, fluorescence labelling methods have provided unique insights into tissue microenvironments. However, many current methods have a variety of limitations that reduce their practical utilization including cost, time and technical complexity. To address these drawbacks, we developed Spatial Photo-inactivation Enhanced Cyclic Target REsolved multiPlexing (SPECTRE-Plex). SPECTRE-Plex is a relatively low cost, end-to-end technique based on a series of methods that significantly improve speed, automation, and resolution of cyclic multiplex immunofluorescence imaging. We describe a representative example of the application of the method by investigating spatial cellular and neighborhood changes in the proximal small intestine between healthy tissue and active celiac disease.